Efektifitas Penggunaan Aplikasi E-Course di Masa Pandemi Terhadap Persiapan Mahasiswa Menghadapi Uji Kompetensi Ners Indonesia - Septian Galuh Winata; Retno Sumara; Erfan Rofiqi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: This study aims to identify the effectiveness of the E-Course in preparing students for the Indonesian Nurse Competency Test Methods: The design used in this study was a pre-post test one group design. The sample of this study were students participating in the Nursing Professional Education Study Program, University of Muhammadiyah Surabaya, who would be prepared to take part in the nurse competency test. This research instrument uses the average standard of Try Out Nurses Competency Test. Before the Nurses Competency Test was carried out, it measured the preparation of students in the Indonesian Nurses Competency Test. The tryout was carried out by AIPNI in September 2019 with a total of 6,379 partic- ipants, the average correct answer was 92.91 out of 180 questions and then processed using the t-test test data analysis technique. Results: there is a significant effect of providing interventions carried out by researchers related to the effectiveness of the use of e-courses on student preparation in facing the competency test with a significant value of p < 0.01 Conclusion: The use of the E-Course for the preparation of the Nurse Competency Test during the pandemic for Nursing Professional Education Study Program students, University of Muhammadiyah Surabaya contributes to the quality of Higher Education Graduates